Designing Agroecology-Based Environmental Accounting Disclosures Through Agricultural Asset Valuation in Indigenous Community-Owned Business Entities - Kurniawan Patma; Ignasisus Dwi Atmana Sutapa; Maria Yosephine Dwi Hayu Agustini (Journal of The Community Development in Asia, 2025)
This study examines the implementation of agroecology-based environmental accounting disclosures through agricultural asset valuation in indigenous community-owned business entities, focusing on BUMMA Mare in Papua. The objective is to evaluate the recognition, measurement, and disclosure of biological assets and agricultural products under PSAK 241 while integrating environmental accounting principles. A qualitative descriptive method was applied using semi-structured interviews with BUMMA Mare management and analysis of financial documents. Results show that BUMMA Mare manages 1,370 areca nut trees, consisting of 623 productive trees valued at IDR 146,405,000 and 747 immature trees valued at IDR 83,664,000. However, its financial statements have not fully implemented PSAK 241, as biological assets and agricultural products remain unrecognized and undisclosed. Furthermore, December’s harvest produced 15,575 kg with an estimated fair value of IDR 2,323,790,000, yet this was not reported in the statements. The study concludes that incorporating agroecology-based environmental accounting improves transparency, strengthens accountability to indigenous stakeholders, and supports both ecological and financial sustainability. This framework offers practical guidance for similar entities in aligning traditional agricultural practices with modern accounting standards.